‘An incredibly vile sport’: campaigns against otter hunting in Britain, 1900–39 - Allen, Daniel; Watkins, Charles; Matless, David (Cambridge University Press, 2016)
Otter hunting was a minor field sport in Britain but in the early years of the twentieth century a lively campaign to ban it was orchestrated by several individuals and anti-hunting societies. The sport became increasingly popular in the late nineteenth century and the Edwardian period. This paper examines the arguments and methods used in different anti-otter hunting campaigns 1900–1939 by organisations such as the Humanitarian League, the League for the Prohibition of Cruel Sports and the National Association for the Abolition of Cruel Sports.